In-situ microparticles for drug delivery - Lee, Tiffany Cai Feng. (2010)
The objective of this project is to determine the effect of formulation parameters on the in vitro drug release of a hydrophilic model drug (metoclopramide hydrochloride) from ISM-systems. A solution of metoclopramide hydrochloride and poly(lactide-co-glycolide) – PDLLA or PDLG 5002 in N-methyl-2-pyrrolideone (NMP) was emulsified into an external oil phase using an Ultra-Turrax homogenizer. After injection into a buffer medium, diffusion of NMP led to polymer precipitation and microparticles formation in situ. UV spectroscopy (UV), Scanning Electron Microscopy (SEM), Gel Permeation Chromatography (GPC) and pH test were performed to relate the drug release of ISM-systems to the surface properties, particle size and polymer degradation/erosion. ISM-systems prepared with 30% PDLLA (polymer/oil phase ratio of 1:1 and 5% drug loading) showed a high initial release of 86.3%. The initial release could be reduced by increasing the polymer concentration, decreasing polymer/oil phase, and drug loading. Under the same formulation conditions, ISM-systems prepared with PDLG 5002 had a much lower initial release (approximately 39.4%) compared to that from PDLLA. In addition, a second solvent – triacetin was added to both ISM-systems to aid in lowering the initial drug release. Since triacetin is partially soluble in water, it has lower affinity for water. This results in slower exchange rate between water and solvent, which was correlated to a slower and lower initial drug release. Hence, from this project, it could be noticed that varying formulation and processing parameters of ISM-systems could affect the initial release.